Detecting co-seismic displacements in glaciated regions : an example from the great November 2002 Denali earthquake using SPOT horizontal offsets - Leprince, Sebastien (2012)
We use SPOT image pairs to determine horizontal offsets associated with the Mw 7.9 November 2002 Denali